Pengaruh Penerapan Metode Debat Terhadap Keaktifan Peserta Didik Dalam Materi Zat Gizi Sumber Zat Pengatur Di SMKN 32 Jakarta - Siti Nurlailia; Rina Febriana; Annis Kandriasari (Program Studi Tata Boga Universitas Negeri Jakarta, 2021)
This study aims to determine the effect of the application of the debate method on the activeness of students in the nutritional content of regulatory substances at SMKN 32 Jakarta, using the Quasi-experimental method. The activeness instrument consists of five lattice indicators of the activeness observation sheet consisting of display, oral, listening, writing and mental with a total of 28 items. The sample of this research was 59 students who were selected by the purposive sampling method. From the data obtained by the experimental class with 29 respondents and the control class with 30 people, the results on visual indicators were 82.74% for activeness in the experimental class and 78.69% for the control class. In the oral indicator as much as 79.59% for activeness in the experimental class and 76.12% for the control class. On the listening indicator as much as 80.12% for activeness in the experimental class and 75.71% for the control class. The writing indicators were 77.98% for activeness in the experimental class and 71.55% for the control class. On mental indicators as much as 75.95% for activeness in the experimental class and 71.67% for the control class. Based on the results obtained, the activeness of students can be ranked according to its indicators, namely indicators of speaking, displaying, writing, listening, and mental. This study found the results of the data analysis were not normally spread, then testing with mann whitney u-test concluded that the method of debate had an effect on the activeness of students in learning the material for the source of regulatory substances. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan metode debat terhadap keaktifan peserta didik dalam materi zat gizi sumber zat pengatur di SMKN 32 Jakarta, menggunakan metode Quasi-eksperimen. Instrumen keaktifan terdiri dari lima indikator kisi-kisi lembar observasi keaktifan yang terdiri dari tampilan, lisan, mendengarkan, menulis, dan mental dengan total 28 butir. Sampel penelitian ini adalah 59 peserta didik yang dipilih dengan metode sampling bertujuan. Dari data yang diperoleh kelas eksperimen dengan jumlah responden 29 orang dan kelas kontrol dengan jumlah 30 orang, mendapatkan hasil pada indikator visual sebanyak 82,74% untuk keaktifan pada kelas eksperimen dan 78,69% untuk kelas kontrol. Pada indikator oral sebanyak 79,59% untuk keaktifan pada kelas eksperimen dan 76,12% untuk kelas kontrol. Pada indikator listening sebanyak 80,12% untuk keaktifan pada kelas eksperimen dan 75,71% untuk kelas kontrol. Pada indikator writing sebanyak 77,98% untuk keaktifan pada kelas eksperimen dan 71,55% untuk kelas kontrol. Pada indikator mental sebanyak 75,95% untuk keaktifan pada kelas eksperimen dan 71,67% untuk kelas kontrol. Berdasarkan hasil yang telah diperoleh keaktifan peserta didik dapat di peringkatkan menurut indikatornya, yaitu indikator berbicara, tampilan, menulis, mendengarkan, dan mental. Penelitian ini mendapatkan hasil analisis data tidak tersebar normal dan dilanjutkan dengan pengujian dengan uji u-man withney, didapatkan hasil bahwa metode debat berpengaruh terhadap keaktifan peserta didik dalam pembelajaran materi zat gizi sumber zat pengatur.